Exploring The Importance And Application Of Licensing Law In Environ-mental Protection In Indonesia - Agung Prasetyo; Slamet Riyanto; Ibrahim Fikma (LEGAL BRIEF, 2024)
Environmental pollution in Indonesia is a serious issue that affects a wide area. This article discusses the impacts of environmental issues, particularly related to the underdevelopment in Indonesia. One preventive measure taken to address environmental pollution is the implemen-tation of a legal permitting policy system. However, there are several issues within the permitting policy, including the mismatch between permitting policies and environmental issues in the re-spective regions. This article discusses the role of permitting laws in supporting environmental preservation and how law enforcement in the field of permitting law can address cases of envi-ronmental degradation. In the research context, the author uses normative and empirical legal research methods. In the main discussion, the article explains the role of permitting laws in sup-porting environmental preservation, including human rights related to the environment and ap-plicable regulations. Furthermore, the author discusses law enforcement in the permitting domain related to cases of environmental destruction, including the types of administrative and criminal sanctions that can be applied